2020
DOI: 10.1007/s42729-020-00337-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Bases of Foliar Silicon-Induced Alleviation of Cadmium Toxicity in Wheat

Abstract: Silicon (Si) is a beneficial nutrient for crop plants, and is gaining increased attention because of its involvement in regulation of abiotic stress tolerance. The present study was carried out to explore the underlying physiological and biochemical mechanisms of foliar Si-induced enhancement in wheat tolerance against cadmium (Cd) stress. Surface sterilized seeds of two wheat cultivars, viz., Inqalab-91 (sensitive) and Sahar-2006 (tolerant), were sown in plastic pots. Foliar application of Si (3 mM) was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 59 publications
(69 reference statements)
1
13
0
Order By: Relevance
“…82 Silicon improved the photosynthetic pigments and protect them from oxidative injury by increasing the synthesis and accumulation of chlorophyll and carotenoid contents. 83,84 In the present study, Si application lessens the oxidative injury in wheat caused by Cd, which might have provoked the chlorophyll and carotenoid contents accumulation in wheat seedling (Table 4).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…82 Silicon improved the photosynthetic pigments and protect them from oxidative injury by increasing the synthesis and accumulation of chlorophyll and carotenoid contents. 83,84 In the present study, Si application lessens the oxidative injury in wheat caused by Cd, which might have provoked the chlorophyll and carotenoid contents accumulation in wheat seedling (Table 4).…”
Section: Discussionmentioning
confidence: 54%
“…In addition, more Cd contents were accumulated in root of both cultivars than those in the shoot ( Figure 4 ). Thind et al (2020) 84 described that Si inhibited the uptake of Cd and decreased its transport in different plant tissues by chelating mechanism. Si being a non-essential nutrient for crop plants can affect plant growth and development in stressed 110 or normal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Universally, the wheat crop is the primary vegetable protein source in the diet of humans, containing a higher protein content than other main grain crops such as maize and rice. The increasing population and food demands further necessitate the increase in wheat production to ensure social stability and future food security [ 2 , 3 ]. In China, wheat is the second-most important food crop after rice and the third-most important crop in total production overall, after maize and rice [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drought causes various changes in crop plants through different morphological, physiological, and biochemical responses [ 11 – 13 ]. Many studies have reported that the defense system of antioxidant was increased through the synthesis of antioxidants such as ascorbate peroxidase (APX) and glutathione reductase (GR), and enzymatic antioxidants such as peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD), which were stimulated to quench the ROS production in plants during drought stress [ 3 , 6 , 14 – 16 ]. Moreover, Datir et al [ 17 ] have reported that the antioxidant enzymes, free proline contents, GB accumulation, MDA, and H 2 O 2 contents were increased under drought induced by polyethylene glycol (PEG) in wheat cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of environmental contamination by Cd are mainly anthropogenic, such as phosphate fertilizers, irrigation with wastewater, metal industries, and heating systems (Sohail et al 2019). Reduced growth, chlorosis, necrosis, phosphorus and nitrogen deficiency, and disturbance of photosynthetic metabolism are the prevalent Cd poisoning-related symptoms (El Rasafi et al 2020;Thind et al 2020). These signs are dependent on the species, the concentration of the metal in the culture medium, and the stage of plant development (Hussain et al 2015).…”
Section: Introductionmentioning
confidence: 99%